2023
DOI: 10.1002/aelm.202201070
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable and Bioabsorbable Polylactic Acid Ferroelectrets with Prominent Piezoelectric Activity

Abstract: Ferroelectrets have promoted a variety of exciting flexible sensors, actuators, and microenergy harvesters. However, most ferroelectrets have been fabricated from non‐degradable petro‐based resins, and thus the recycling of these materials constitutes a big challenge. This article reports biodegradable and bioabsorbable ferroelectret films made from polylactic acid (PLA) resins for highly sensitive transducer applications, which can operate either in piezoelectric 33 or 31/32 mode. By modification of the micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…[150,151] Polylactic acid (PLA) is a biodegradable biopolymer with piezoelectric properties, although these properties are relatively weak. [152] To enhance piezoelectric properties, an effective approach was taken to incorporate an inorganic piezoelectric nanomaterial called KNN into the PLA matrix to construct a piezoelectric PLA/KNN@polydopamine (PLA/KNN@PDA) composite nanofiber scaffold. [153] As the KNN@PDA mass ratio (0-50%) increases, the peak output voltage of the nanoscaffold triggered under pressure (0.5 N, 10 Hz) increased sharply, from 0.52 V to 17.9 V. The output current increased from 0.12 to 2.6 μA, and the output efficiency was significantly improved.…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…[150,151] Polylactic acid (PLA) is a biodegradable biopolymer with piezoelectric properties, although these properties are relatively weak. [152] To enhance piezoelectric properties, an effective approach was taken to incorporate an inorganic piezoelectric nanomaterial called KNN into the PLA matrix to construct a piezoelectric PLA/KNN@polydopamine (PLA/KNN@PDA) composite nanofiber scaffold. [153] As the KNN@PDA mass ratio (0-50%) increases, the peak output voltage of the nanoscaffold triggered under pressure (0.5 N, 10 Hz) increased sharply, from 0.52 V to 17.9 V. The output current increased from 0.12 to 2.6 μA, and the output efficiency was significantly improved.…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…In recent years, researchers have paid much attention to the electroconductive and piezoelectric properties and behavior of PLA-based materials for their potential to mimic bone tissues. Ferroelectrets films created from PLA can be used to prepare biosensors involved in the development and growth of cells [212]. A biphasic layered structure was synthesized from electrospun mats of piezoelectric polyvinylidene fluoride/PLA embedded in a terpolymer hydrogel of alginate/gelatin/polypyrrolegrafted-gelatin to form osteon-mimetic samples [213].…”
Section: The Emphasis On Recent Advances In Pla Derivativesmentioning
confidence: 99%
“…Biopiezoelectric materials, such as barium titanate/ PLA composites, mimicked the microenvironment of bone tissue successfully and guided it through regeneration [214]. Concerning the injectability of PLA-based polymers, the scientific community has found that these biomaterials can act as an aqueous reservoir to treat defect shapes in bone tissue engineering because they can be molded easily and exhibits good biodegradability, rheology, selectivity, and targeting capability [212,[215][216][217].…”
Section: The Emphasis On Recent Advances In Pla Derivativesmentioning
confidence: 99%
“…Figure a shows a life cycle of cellular polylactic acid (PLA) ferroelectrets, illustrating an environmentally friendly closed-loop period from functional material production to the final disposal. The specific fabrication process and electromechanical properties characterization results of the PLA ferroelectrets have been announced in our previous work, so the present paper will give a brief description and focus on the acoustic performance of the electroacoustic transducers, involving microphones (receiver) and loudspeakers (emitter). Figure b demonstrates the potential application scenarios of the acoustic sensor in a smart home.…”
Section: Introductionmentioning
confidence: 99%